Dual Function of Silver Nanoparticles as Matrix Extracell Removal and Antimicrobial Agent in Polymycrobial Biofilms - Mei Shirli Yasinta; Hera Lisna Ginawati; Nira Ambar Arum; Harini Nur Hikmah; Sri Sumarsih; Mochamad Zakki Fahmi; Afaf Baktir (Universitas Gadjah Mada, 2021)
Candida albicans often form polymicrobial biofilms along with pathogenic microbes. Silver nanoparticles (AgNPs) were well known to have strong antimicrobial activity. However, their effect on polymicrobial biofilms and the mechanism has never been reported. This study aimed to synthesize AgNPs and study their effects on polymicrobial biofilm represented by C. albicans–E. coli biofilm. Polymicrobial biofilms, formed by clinical isolates of C. albicans and E. coli, were developed from the standardized suspensions of each strain by culturing flat-bottom 96-well microtiter plates for 48 h, then treated with AgNPs. Cell viability was assessed using the tetrazolium salt reduction assay; the extent of biofilm formation was measured by crystal violet staining. AgNPs reduced the polymicrobial biofilm in two ways: by degrading the extracellular matrix and killing both C. albicans and E. coli. The results showed AgNPs is a potential new approach for developing potent anti-biofilms.